Asset and Liability Management (ALMA), Islamic Corporate Social Responsibility (ICSR), and Zakat Collectively Contribute to Increasing Company Value, as Seen from the Perspective of Sharia Economic Theory (SET) - Ismawati Ismawati; Lince Bulutoding; Retno Fitrianti; Ainul Fatha Isman (LPPM Universitas PGRI Sumatera Barat, 2025)
Increasing the value of a banking company based on Islamic corporate theory is not only about financial profit, but also about sustainability, justice, and blessings in business. This study aims to reveal and analyze the role of Asset and Liability Management (ALMA) as a form of accountability to humans, Islamic Corporate Social Responsibility (ICSR) as a form of accountability to nature, and zakat as a form of accountability to God in optimizing company value based on Islamic Corporate Theory. This study is a quantitative study with a causal associative research type, the population in this study is 14 Islamic Commercial Banks in Indonesia. Data analysis uses multiple linear regression with e-Views as an analytical tool. The results show that Asset and Liability Management (ALMA) and Islamic Corporate Social Responsibility (ICSR) have a positive effect on the value of Islamic banking companies, while zakat does not affect the value of Islamic banking companies; this is because the role of Islamic banking in collecting zakat funds is not optimal. Simultaneously, 96% of company value can be explained by three independent variables: ALMA, ICSR, and Zakat. Meanwhile, other variables outside the model explain the remaining 4%. This figure indicates a significant influence, meaning that ALMA, ICSR, and Zakat, if properly managed in Islamic banking, can become pillars for increasing the value of Islamic banking companies. The novelty of this research is that these three pillars should be a focus for Islamic banks to increase company value, particularly in strengthening their role in collecting zakat funds.